AN ANALYSIS OF TASK-BASED LANGUAGE TEACHING (TBLT) APPROACH USED BY THE TEACHER IN WRITING SKILL AT BINA CITA MANDIRI (BCM) COURSE & COUNSELING - Bahing Bahing; Mayang Meilatina; Bahing (Journal of Innovation Research and Knowledge, 2026)
This study was an Analysis of Task-Based Language Teaching (TBLT) Approach Used by The Teacher in Writing Skill at Bina Cita Mandiri (BCM) Course & Counseling. It is done by lecturers of Magister of English Language Education, Graduate Program, University of Palangka Raya. It was conducted by (I) Dr. Bahing, S.PD. M.PD. (II) Dr. Mayang Meilantina, M.Sc. Task-Based Language Teaching (TBLT) is a communicative approach to language teaching and learning that views language primarily as a tool for communication rather than as a subject of study. In this approach, learners engage with the language through meaningful tasks that are carefully designed and sequenced, allowing them to acquire and use the language in real-world, communicative contexts. The purpose of the research was to know how the teacher at BCM Course & Counseling apply Task-Based Language Teaching (TBLT) approach in teaching writing skill, and to know the obstacles are encountered in teaching English writing using the Task-Based Language Teaching (TBLT) method.The researcher used descriptive qualitative method. Three instruments were utilized observation, interview, and documentation for collecting the data. The subject was the English teacher at 5th Grade in BCM Course & Counseling, Palangka Raya. The researcher obtained the teacher at Bina Cita Mandiri (BCM) Course & Counseling utilized the TBLT approach by integrating a series of well-designed tasks into the English writing curriculum, which align with real-world activities. Tasks such as arranging sentences, translating words, and filling in blanks worksheets task from online resources like ISL Collective and Live Worksheet. Group discussions form a core part of the TBLT approach at BCM. Students are divided into small groups, and each group works collaboratively on the assigned writing tasks. The problems that the researcher found while observing and interviewing the teachers. There were students' cognitive abilities, difference in curricula, student attendance, motivations, and limited practice opportunities